2020
DOI: 10.3389/frobt.2020.00034
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Use of Temporal-Difference Incremental Delta-Bar-Delta for Real-World Predictive Knowledge Architectures

Abstract: Predictions and predictive knowledge have seen recent success in improving not only robot control but also other applications ranging from industrial process control to rehabilitation. A property that makes these predictive approaches well suited for robotics is that they can be learned online and incrementally through interaction with the environment. However, a remaining challenge for many prediction-learning approaches is an appropriate choice of prediction-learning parameters, especially parameters that co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Not only do these adaptive step-sizes improve learning, they can also provide useful information about the operation of an agent (Günther et al, 2019). Learned step-size values can also detect anomalies in the agent's observation stream, including those that indicate a hardware or sensor failure of the agent (Günther et al, 2020).…”
Section: Feature Relevance: a Self-assessment Of Explanatory Variablesmentioning
confidence: 99%
“…Not only do these adaptive step-sizes improve learning, they can also provide useful information about the operation of an agent (Günther et al, 2019). Learned step-size values can also detect anomalies in the agent's observation stream, including those that indicate a hardware or sensor failure of the agent (Günther et al, 2020).…”
Section: Feature Relevance: a Self-assessment Of Explanatory Variablesmentioning
confidence: 99%
“…For example, Unexpected Demon Error (UDE), can be used to gauge how 'surprising' a given observation is to an agent (White, 2015). By examining the surprise, we can gauge how current experience relates to past experiencesfor example, detecting faults in a system (Günther et al, 2018).…”
Section: Proposal: Evaluate Feature Relevancementioning
confidence: 99%
“…Recent research has shown the benefit of predictions when used for prosthetic limbs (Gu¨nther et al, 2018(Gu¨nther et al, , 2020Pilarski et al, 2013;Sherstan & Pilarski, 2014), with Sherstan and Pilarski (2014) demonstrating that an abundant number of GVFs can be learned and maintained with reasonable computational resources, allowing these techniques to be used in mobile robots. Such GVF predictions have been demonstrated to be useful for prosthetic limbs in several ways.…”
Section: Prosthetic Armsmentioning
confidence: 99%
“…The Modular Prosthetic Limb (MPL), a robot arm with many degrees of freedom and sensors used for research in prosthetic limbs (Günther et al, 2020). …”
Section: Bridging Gvf and Affordance Applicationsmentioning
confidence: 99%